Unveiling Acehnese Subject Properties: A Typological Analysis of Grammatical Relations and Behaviors - Juliana, Juliana; Mulyadi, Mulyadi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
This study provides a comprehensive typological analysis of the grammatical characteristics of subjects in Acehnese, focusing on the unique subject properties in this lesser-studied language. Utilizing a qualitative descriptive methodology, data were sourced from Acehnese language corpora and existing grammatical accounts. Selective sampling identified 200 sentences, which were analyzed across six syntactic parameters: fronting, floating quantifier, control, relativization, word order, and interrogative sentence construction. The analysis employed distributional and permutation techniques to identify patterns and deviations in subject behavior. Findings reveal that Acehnese subjects, typically noun phrases preceding verbs, can function as patients in transitive clauses without distinct marking. Crucially, Acehnese does not conform to a single 'subject' relation; instead, syntactic processes differentiate between Actor and Undergoer roles. This non-conformity to conventional typological theories underscores the unique syntactic structure of Acehnese. The results highlight the flexible and complex nature of grammatical relations in Acehnese, challenging traditional notions of subjecthood. This study contributes significantly to the broader understanding of syntactic diversity, emphasizing the need for refined and flexible theoretical frameworks in grammatical relations. By illuminating the intricate grammatical systems in Acehnese, the research underscores the importance of adaptable models in linguistic theory to accurately capture the diversity and complexity inherent in human languages. This insight is crucial for advancing linguistic typology and enhancing comparative linguistic analysis in the Southeast Asian region​.